2008
DOI: 10.1002/cbdv.200890101
|View full text |Cite
|
Sign up to set email alerts
|

Odorant–Receptor Interactions and Odor Percept: A Chemical Perspective

Abstract: Receptor-ligand interaction models are generally based on a 'lock and key' concept. How far this holds true for olfactory receptors and odor molecules is currently uncertain. Here, we have investigated the response of a human olfactory receptor, OR1D2, to a broad array of odorants and found that there is no simple, direct correlation between a molecule's ability to activate this receptor and the odor impression elicited in the brain. In a parallel study on specific anosmia, we have found no evidence for odor-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…To identify specific stimuli for OR4D1 and OR7A5, we used the same experimental strategy that we had successfully employed in the past to match human OR-ligand pairs (17,38,(55)(56)(57)74). Given the poor OR surface expression rate typically observed in heterologous cells (47), careful evaluation of single cell Ca 2ϩ responses is imperative, making this an "ultra-low throughput" assay that is neither applicable to the full repertoire of human ORs 5 nor suitable for large scale ligand screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify specific stimuli for OR4D1 and OR7A5, we used the same experimental strategy that we had successfully employed in the past to match human OR-ligand pairs (17,38,(55)(56)(57)74). Given the poor OR surface expression rate typically observed in heterologous cells (47), careful evaluation of single cell Ca 2ϩ responses is imperative, making this an "ultra-low throughput" assay that is neither applicable to the full repertoire of human ORs 5 nor suitable for large scale ligand screening.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of semiconfluent HEK293 cells with fulllength PCR products cloned into pcDNA3 vectors (Invitrogen) was conducted using the calcium phosphate precipitation technique, and transfection efficiency was monitored as described (17,38). In some experiments, we coexpressed RTP1, RTP2, and REEP1 to promote functional cell surface expression (47).…”
Section: Recombinant Odorant Receptor Expressionmentioning
confidence: 99%
“…141,142 To date, the type of odor elicited by a volatile compound cannot be reliably predicted by the structure of the molecule. 143 …”
Section: Smellmentioning
confidence: 99%
“…In a parallel study on specific anosmia, no evidence was found for odorant-specific anosmia to either musk or amber, but rather to specific molecules within these categories. 13 Genotypic variation in OR7D4 accounts for a significant proportion of the valence (pleasantness or unpleasantness) and intensity variance in perception of steroidal odours. Studies of the OR7D4 receptor and androstenone (27, Figure 10.6) perception demonstrated a link between the function of a human odorant receptor in vitro and odour perception.…”
Section: Specific Anosmiasmentioning
confidence: 99%
“…No simple scheme relating odorant chemical structure or olfactory receptor activation to perception is likely to be of broad explanatory value without incorporating prior empirical knowledge of psychophysical responses to the odorant ligands being considered. 13,14 These issues have recently been reviewed. 15 Human olfactory ability is often viewed as of minor importance relative to other distal sensory modalities such as vision or audition.…”
Section: Introductionmentioning
confidence: 99%